Seroprevalence of Zika Virus among Forest Fringe Communities in Peninsular Malaysia and Sabah: General Population-Based Study - Khoo, Hooi-Yuen; Lee, Hai-Yen; Khor, Chee-Sieng; Tan, Kim-Kee; bin Hassan, Mohd Rohaizat; Wong, Chin Mun; Agustar, Hani Kartini; Samsusah, Nadia Aqilla; Rahim, Syed Sharizman Syed Abdul; bin Jeffree, Mohd Saffree; Yusof, Nur Athirah; Haron, Noor Ain; et al. (The American journal of tropical medicine and hygiene, 2022)
Zika virus (ZIKV) has had a history in Malaysia since its first isolation in 1966. However, it is believed that the immunity status among forest fringe communities has been underreported. We conducted cross-sectional surveillance of forest fringe communities from 10 Orang Asli villages and their peripheral communities in Perak, Pahang, and Sabah in Malaysia. A total of 706 samples were collected from 2019 to 2020 and screened for ZIKV exposure using an anti-ZIKV IgG ELISA kit. A neutralization assay against ZIKV was used to confirm the reactive samples. The seroprevalence results reported from the study of this population in Malaysia were 21.0% ( n = 148, 95% CI, 0.183–0.273) after confirmation with a foci reduction neutralization test. The presence of neutralizing antibodies provides evidence that the studied forest fringe communities in Malaysia have been exposed to ZIKV. Multivariate analysis showed that those older than 44 years and those with an education below the university level had been exposed significantly to ZIKV. In addition, higher seropositivity rates to ZIKV were also reported among secondary school students from Bentong (Pahang) and residents from Segaliud (Sabah). No associations were identified between Zika seropositivity and gender, household size, house radius to the jungle, and income level. The presence of neutralizing antibodies against ZIKV among the study population might indicate that the causative pathogen had already circulated widely in forest fringe regions. Intervention for vector control, protection from mosquito bites, and awareness improvement should be encouraged in this population.